Registro histórico de los cines en el centro de Quito - Borja Villavicencio, Ingrid Mariela (2015)
Communication has been understood as the process that develops between two or more people who transmit certain information, in order to establish a mutual understanding or agreement. However we just cannot describe it as simple as this because communication not only constitutes processes of dialogue, agreement and understanding but it composes an extensive system of processes and media and also covers a universe of social activities among human beings, which also determine the cultural identity of nations and peoples. One of the media that allow interaction between subjects is the cinema, which is a tool to establish communication bridges with elements of significance, so the large number of signs that make up the production and viewing of film developing activity mired in a cultural and social environment. Semiotics as a discipline of communication describes the different communication processes of signs and symbols that are linked themselves in cinema, hence the semiotic is not limited to systems of signs in his theory but the exercise thereof in their social context and meaning in social relations. Research on the Historic Register theaters Quito has a theoretical basis for communication through semiotics to analyze the different signs that form a context within the city.